Optimizing indoor digital holography for photovoltaic surface analysis: a novel approach for solar PV testing conditions - Abdullahi Bako; Bunyarit Voochaiphum; S. Suchat; Prathan Buranasiri (My University, 2025)
The sun is a clean, inexhaustible, free energy source, and it is environmentally safe. The rapid expansion of the solar photovoltaic (PV) industry demands innovative quality control techniques for defect detection and efficiency optimization of solar cells. Traditional methods such as electroluminescence, photoluminescence, and infrared thermography have limitations in detection resolution, real-time monitoring, and surface characterization. In this research, a novel approach digital holography-based non-contact method for detecting and analyzing defects in solar cells, such as micro-structural defects, surface roughness, dust, scratch, and cracks, was investigated. Laser module was used as our light source to optimize indoor test conditions. An integrated recognition system was developed to automate and improve accuracy using real hologram images. Reconstruction images and Fourier transforms were used to extract the phase and amplitude across the solar PV cell. This preserved the module’s integrity and providing detailed defect information from the solar surface.
Keywords: Photovoltaic System Optimization Techniques; Digital Holography and Microscopy; Electrowetting and Microfluidic Technologies